Fine‐tuned broad binding capability of human lipocalin‐type prostaglandin D synthase for various small lipophilic ligands. Issue 6 (11th February 2014) - Kume, Satoshi; Lee, Young-Ho; Nakatsuji, Masatoshi; Teraoka, Yoshiaki; Yamaguchi, Keisuke; Goto, Yuji; Inui, Takashi
Abstract : The hydrophobic cavity of lipocalin‐type prostaglandin D synthase (L‐PGDS) has been suggested to accommodate various lipophilic ligands through hydrophobic effects, but its energetic origin remains unknown. We characterized 18 buffer‐independent binding systems between human L‐PGDS and lipophilic ligands using isothermal titration calorimetry. Although the classical hydrophobic effect was mostly detected, all complex formations were driven by favorable enthalpic gains. Gibbs energy changes strongly correlated with the number of hydrogen bond acceptors of ligand. Thus, the broad binding capability of L‐PGDS for ligands should be viewed as hydrophilic interactions delicately tuned by enthalpy–entropy compensation using combined effects of hydrophilic and hydrophobic interactions. Abstract : The hydrophobic cavity of L‐PGDS is vital to binding of various lipophilic ligands. The 18 binding systems of L‐PGDS with ligands were thermodynamically studied by ITC. The classical hydrophobic effect stabilized most complexes. All complexes were driven by enthalpy due to the formation of intermolecular H bonds. The broad binding of L‐PGDS is fine‐tuned by hydrophilic and hydrophobic interactions.